Reformas a la prescripción del pago del impuesto a la herencia a favor de las personas discapacitadas a fin de garantizar su desarrollo Económico Y Social - Gallegos Jaramillo, María Augusta (2015)
The rights of people with disabilities specialty from inheritance rights, have evolved according to principles such as the escalation of their rights, so that the estate tax, is exempt for this vulnerable and priority sector. The Constitution of the Republic of Ecuador, week in Art. 47, number 4 tax exemptions, which exempt from such payment, the statute of limitations for applying domain is not within the undivided inheritance rights of communities, where there are people with special abilities, which restrict their rights directly economic and social. It is important that the State guarantees fundamental rights to social and economic inclusion by prescription where there is a disabled person in an undivided estate in order to protect economic and social rights of this sector. This thesis seeks to ensure the principles and guarantees established in the Constitution and international instruments to which our state is a signatory. For the rights of non-discrimination and social and economic equality of the disabled sector to inheritance rights are met.